Knowledge about public health programs in Brazil and their correlation with the Brazilian Unified Health System: short communication (Research, Society and Development, 2022)
Objective: To know the notable public health programs in Brazil and their associations with the Unified Health System. Methods: This is a short communication about important public health programs in Brazil. Scientific articles published in the last ten years were used. The choice was made through searches in scientific databases. Results: It was noted that the user's understanding can be an indispensable source of knowledge for designing evaluations of the care process as well as the results obtained with the applicability of certain models and/or assistance programs. Therefore, despite the adversities, which are not few, the Unified Health System has several public health programs considered international references. Conclusion: The programs mentioned, as well as other existing ones, must be carried out effectively and in accordance with the needs and epidemiological specificities of each territory. However, there are significant services that support health promotion, prevention of risks, injuries, and diseases, understanding morbidity, reducing years lost due to disability and increasing the quality of life of individuals and populations.